Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Dilla University - International Livestock Research Institute; Dilla University (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
MoU Dilla University and International Livestock Research Institute